SARS-CoV-2-mRNA Booster Vaccination Reverses Non-Responsiveness and Early Antibody Waning in Immunocompromised Patients – A Phase Four Study Comparing Immune Responses in Patients With Solid Cancers, Multiple Myeloma and Inflammatory Bowel Disease - Wagner, Angelika; Garner-Spitzer, Erika; Schötta, Anna-Margarita; Orola, Maria; Wessely, Andrea; Zwazl, Ines; Ohradanova-Repic, Anna; Weseslindtner, Lukas; Tajti, Gabor; Gebetsberger, Laura; Kratzer, Bernhard; Tomosel, Elena; et al. (Frontiers in Immunology, 2022)
Background: Individuals with secondary immunodeficiencies belong to the most vulnerable groups to succumb to COVID-19 and thus are prioritized for SARS-CoV-2 vaccination. However, knowledge about the persistence and anamnestic responses following SARS-CoV-2-mRNA vaccinations is limited in these patients. Methods: In a prospective, open-label, phase four trial we analysed S1-specific IgG, neutralizing antibodies and cytokine responses in previously non-infected patients with cancer or autoimmune disease during primary mRNA vaccination and up to one month after booster. Results: 263 patients with solid tumors (SOT, n=63), multiple myeloma (MM, n=70), inflammatory bowel diseases (IBD, n=130) and 66 controls were analysed. One month after the two-dose primary vaccination the highest non-responder rate was associated with lower CD19+ B-cell counts and was found in MM patients (17%). S1-specific IgG levels correlated with IL-2 and IFN- responses in controls and IBD patients, but not in cancer patients. Six months after the second dose, 18% of patients with MM, 10% with SOT and 4% with IBD became seronegative; no one from the control group became negative. However, in IBD patients treated with TNF- inhibitors, antibody levels declined more rapidly than in controls. Overall, vaccination with mRNA-1273 led to higher antibody levels than with BNT162b. Importantly, booster vaccination increased antibody levels >8-fold in seroresponders and induced anamnestic responses even in those with undetectable pre-booster antibody levels. Nevertheless, in IBD patients with TNF- inhibitors even after booster vaccination, antibody levels were lower than in untreated IBD patients and controls. Conclusion: Immunomonitoring of vaccine-specific antibody and cellular responses seems advisable to identify vaccination failures and consequently establishing personalized vaccination schedules, including shorter booster intervals, and helps to improve vaccine effectiveness in all patients with secondary immunodeficiencies. Trial registration: EudraCT Number: 2021-000291-11